Avaliação da anodização em pistão automotivo de liga de alumínio fundido para melhorar resistência a corrosão - Nascimento, Mariana dos Santos do (2022)
The present study evaluated the application of sulfurictartaric anoding treatment in AlSi alloy from paraná industry in order to mitigate piston corrosion and make the product more competitive in the market. The alloy and its structural integrity and consequently the operation of the engine, can be greatly impaired by the fatigue cracks resulting from corrosion that has the possibility of spreading quickly in the part. The method of anodentation applied, consisted of placing in a tank of insulating material a mixture of acids, together with a method connected to a rectifier, which produced an electric current. The sample was immersed in the bath and the acid induced the formation of macro porosities with a rough inner surface, and the outer part of these cells becomes more resistant to acid and improves their properties. For the present work, a study was made on the effects that sulfurictartaric anoding causes in aluminum and silicon alloy used in automotive pistons, specifically pistons manufactured by the metallurgical industry, located in the city of Guarapuava in the state of Paraná, which sought to understand through research whether the method contributes satisfactorily in mitigating the corrosion of these pistons in its application, this is the main aspect to be achieved so that the material can compete commercially with competitors from Europe. In general, the results of the present study indicated that in general the alloy samples were benefited by the anoding treatment. Corrosion mitigation is related to the thickness of the anodic layer formed, but not only the thickness of the layer was determinant for corrosion resistance, the sample that had the best performance was not the one with the highest layer thickness formed. It was strongly influenced by factors such as porosity and adhering, intrinsic to the sample and the environment in which it is exposed. The corrosion of the sample was also related to the time of exposure of the alloy to the acid bath, following a proportional trend. But the time alone also did not determine the best performance. The set of variables added with the change in the concentrations of the reagents used, suggested the bath with better result as being the one that contained tartaric acid in higher concentration in relation to sulfuric acid. The applied potential that showed the best result was the highest potential, of 20V, as well as citations in the literature.